School-Based Speaking Habituation in EFL Contexts: Investigating the English Friday Let’s Talk Program in Indonesian Secondary Education - Evi Nurul Mubarokah; Muhammad Nafi Annury (FOSTER: Journal of English Language Teaching, 2026)
This qualitative case study investigated how the English Friday Let’s Talk program was implemented as a school-based speaking habituation program at Al-Azhar 16 Islamic Senior High School, Semarang, and how students perceived the program. The study involved one English teacher, five English Talent Program students, and five regular students who participated in the program. Data were collected through semi-structured interviews, observation, and supporting documentation, then analyzed using Miles and Huberman’s interactive model consisting of data reduction, data display, and conclusion drawing and verification. The findings show that the program was implemented through structured weekly topic assignment, writing tasks, oral/reading activities, video performances, English communication practice every Friday, school policies such as the No English, No Service rule, teacher monitoring and feedback, and in-house training for non-English teachers. Students perceived improvements in speaking fluency, vocabulary, pronunciation, confidence, sentence construction, and language habituation through their participation in the program. English Talent Program students reported stronger technical speaking development and spontaneity, whereas regular students emphasized increased courage and confidence. The main challenges were limited vocabulary, pronunciation and grammar anxiety, fear of negative evaluation, uneven proficiency, and limited English use among non-English teachers. The study implies that a school-based English-speaking program can support communicative practice through preparation, performance, policy, feedback, and teacher development.